DISTRESS SALES AS LIVELIHOOD STRATEGY: COMMERCIALIZATION AND THE PERSISTENCE OF POVERTY AMONG WIDOWED FARMERS IN CONFLICT-AFFECTED NIGERIA - Shehu, Abbas; Bulus, Barnabas; Kadafur, Muhammad Ibrahim; Mohammed, Ragada’a; Bakari, Aishatu Usman; Oseni, Muinat Omowumi; Bala, Rashida Abdulmumini (Applied Studies in Agribusiness and Commerce, 2026)
Widowhood is a catastrophic event for women farmers at any stage of their lives, with serious implications for their well-being. We examines the effect of household commercialization on poverty of widowed cowpea farmers in North-east Nigeria. Multistage dsampling procedure was employed which arrived at 525 respondents. The Data were collected using structured questionnaire and analysed using both descriptive and inferential statistic (muliple regression). The result revealed that Household commercialization index (HCI) was 55.44% and 54.19% of the IDPs and host communities respectively. The average progress out of poverty index (PPI) score was lower for IDP farmers (33.55) compared to host community farmers (42.96) with homogeneity in both. Explanatory variables influencing PPI explained 35.30% of its variation, Legume farming experience and value harvest were found to be improving PPI, Household size and IDP status were reducing the PPI. The HCI was explaining 4.7% of Poverty of widowed cowpea farmers, and the HCI had inverse relationship with poverty. All in all, widowed cowpea farmers’ household commercialization increases poverty by 0.126, with heterogeneity among households with higher legume farming experience, lower household sizes, IDPs host communities and higher value of cowpea which experienced less poverty in the study area. Strengthening cooperative development, promoting value addition of cowpea products, expanding access to financial services and targeted support for widowed farmers is hence recommended.